THE INTEGRATION OF BANJAR PHILOSOPHY AND THE QUR'AN: A SOLUTION FOR THE RESILIENCE OF THE STRAWBERRY GENERATION - ANWAR FAHMI; Rendy Pradana (IAIN Bone, 2026)
The contemporary digital era has given birth to the phenomenon of the